Client congruence in therapy and its association with mindfulness and the therapeutic relationship - Ivtzan, Itai; Joseph, Stephen (Academic Journals, 2017)
In order to investigate clients’ role in the mutuality of therapeutic encounter, this pilot study examined data from 49 participants who had undergone at least three sessions of therapy. The participants completed the Working Alliance Inventory and the Kentucky Inventory of Mindfulness Skills. As hypothesised, higher levels of mindfulness were associated with enhanced working alliance. All three dimensions of the working alliance (quality of therapeutic bond, agreement on tasks, and agreement on goals) were found to be associated with mindfulness. These results suggest that it would be worthwhile to develop future longitudinal research on the relationship between client variables and the development of therapeutic encounter.